Community-Onset Extended-Spectrum β-Lactamase–Producing Enterobacteriaceae Invasive Infections in Children in a University Hospital in France. Issue 12 (March 2016) - Toubiana, Julie; Timsit, Sandra; Ferroni, Agnès; Grasseau, Marie; Nassif, Xavier; Lortholary, Olivier; Zahar, Jean-Ralph; Chalumeau, Martin
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Limited data is available on pediatric community-onset infections with extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE), but such infections may affect both the efficacy of empiric antibiotic therapy and the rational use of antibiotics. We retrospectively analyzed data from 2007 to 2012 for all children ≤16 years old with a positive ESBL-PE strain from usually sterile sites within 48 hours of admission in a tertiary hospital in France. We analyzed healthcare- and community-associated infections among community-onset infections. In total, 3612 Enterobacteriaceae isolates were collected; the prevalence of ESBL-PE infection increased over the study period, from 2.4% to 5.1% ( P < 0.001). Among the 90 children with a first community-onset ESBL-PE infection, 58% (n = 52) had a healthcare-associated infection, and 87% of isolates were susceptible to amikacin. As compared with patients with community-associated infections, those with healthcare-associated infections had fewer urinary tract infections (UTIs) (86% vs 97%) and Escherichia coli infections (35% vs 84%) and more Klebsiella pneumoniae infections (46% vs 8%). Inappropriate empiric treatment was prescribed for 54 patients (64%), but a favorable outcome was observed in 46 of 49 (94%) and 1 of 5 (20%) patients with UTIs and non-UTIs, respectively ( P < 0.001). Among patients with community-associated infections, 85% had at least 1 risk factor for ESBL-PE infections. In conclusion, the prevalence of community-onset ESBL-PE infections doubled during the study period. These infections mainly occurred among children with healthcare-associated criteria or identified risk factors. Amikacin is an alternative to carbapenems for empiric treatment because most of these infections involved urinary tract and susceptible isolates.